Da entrevista à observação da ação : uma tendência realista-fabular no cinema brasileiro pós-2010 - Feix, Daniel (2019)
This study aims to analyze the changing from the interviews documentarie’s trend, in the brazilian movies of the 21st century, to those films in witch the meeting between I (moviemaker and his team) and the Other (characters) use the observation of action as a resource. With the camara afar, capturing the intrigue that was only told as of before (KRACAUER, 1997), the feature films from Minas Gerais A falta que me faz (2010), O céu sobre os ombros (2011) and Girimunho (2012) gradually implement that change. In this study, these aforementioned movies are analyzed starting of their key-sequences, that display the incorporation of extrafield elements to the image (BURCH, 2015), stablish a “presence effect” (RAMOS, 2008; DIDI-HUBERMAN, 2010) and a “fabulation” (GUIMARÃES, 2001; DELEUZE, 2013) witch reconfigures the bonds between characters and the spaces they live in. These characteristics mould the realistic-fabulate trend in brazilian movies of this period.